Pemanfaatan Ekstrak Daun Beluntas (Pluchea indica) Sebagai Bahan Aktif Deodoran Spray Alami - Maulin Hayatun Qariza; Ratna Sari; Elfiana Elfiana; Ratni Dewi; Nir Fathiya (Politeknik Negeri Lhokseumawe, 2026)
Body odor is a common problem experienced by people in tropical climates such as Indonesia. Continuous use of chemical-based deodorants risks causing irritation and other skin disorders, thus driving the need for natural alternatives that are safer and more environmentally friendly. This study aims to obtain the optimal powder size and soaking time in producing beluntas leaf extract as well as the optimal concentration as a spray deodorant. Extraction was carried out through the maceration method with variations in powder size of 60/80, 80/100, 100/120, 120/140 and 140/160 mesh and soaking times of 2, 3, 4, 5 and 6 days. Parameters analyzed included yield, residual solvent content, flavonoid content, and antioxidant activity (IC₅₀). The best extract was then formulated into a spray deodorant with concentrations of 10%, 15%, 20%, 25% and 30%, then tested for physical stability, organoleptic properties, and antibacterial activity against Staphylococcus epidermidis. The results showed that 100/120 mesh powder with a five-day soaking time produced the best extract with a yield of 11.75% and a residual solvent content of 0.73%. The extract contains active flavonoids with very strong antioxidant activity (IC₅₀ = 3.79 ppm). The deodorant formulation with a 25% concentration provided the most optimal physical and antibacterial performance, thus having the potential to be developed as an effective and safe natural deodorant product.